De medewerkers van het muzikale hoorspel "De familie Doorsnee". Resp. 3de, 4de en 5de van rechts Ibo, Blok, Brusse, (1955)
De medewerkers van het muzikale hoorspel "De familie Doorsnee". Resp. 3de, 4de en 5de van rechts Ibo, Blok, Brusse,